Biff, chip and kipper stories: group/guided reading notes stage 4 (oxford reading tree) - Page, Thelma (Oxford University Press Karachi, 2011)
"A wonderful mixture of stories including familiar settings to reassure children, and fantasy adventures to inspire them. Packed full of humour, drama, detailed illustrations and endearing characters to motivate every child Carefully levelled to ensure the gradual development of early reading skills - great for children with English as an additional language."--Publisher's website